Parâmetros biológicos da lagarta falsa-medideira em cultivares de algodoeiro com as proteínas Cry1Ac e Cry1F - Viana, Daniela De Lima; Netto, Jacob Crosariol; Aguirre-gil, Oniel Jeremías; Busoli, Antonio Carlos (Embrapa Informação TecnológicaPesquisa Agropecuária Brasileira, 2014)
The objective of this work was to evaluate the effects of transgenic cotton cultivars expressing the Cry1Ac and Cry1F proteins, on the biological parameters of soybean looper (Chrysodeixis includens). Neonate larvae were fed during the entire larval phase with leaves from transgenic cultivars and their conventional isolines. In the Nuopal (Bollgard I) cultivar (Cry1Ac), 62% of larvae survived and became normal pupae. The FM 975 (WideStrike) cultivar (Cry1Ac and Cry1F) is lethal to first-instar larvae, with 100% mortality.

O objetivo deste trabalho foi avaliar os efeitos de cultivares transgênicas de algodoeiro que expressam as proteínas Cry1Ac e Cry1F, nos parâmetros biológicos da lagarta falsa-medideira (Chrysodeixis includens). Lagartas neonatas foram alimentadas durante toda a fase larval com folhas de cultivares transgênicas e de suas isolinhas convencionais. Na cultivar Nuopal (Bollgard I) (Cry1Ac), 62% das lagartas sobreviveram e se transformaram em pupas normais. A cultivar FM 975 (WideStrike) (Cry1Ac e Cry1F) é letal para lagartas de primeiro instar, com 100% de mortalidade.
Biological parameters of soybean looper in cotton cultivars with the Cry1Ac and Cry1F proteins
Keywords: Bacillus thuringiensis; Chrysodeixis includens; Gossypium hirsutum; Bollgard I; planta geneticamente modificada; WideStrike; Bacillus thuringiensis; Chrysodeixis includens; Gossypium hirsutum; Bollgard I; genetically modified plant; WideStrike